BEYOND DECODING: INTEGRATING COMMUNICATIVE LANGUAGE TEACHING (CLT) METHOD TO ENHACE MAHARAH AL-QIRA’AH - Muh Jabir; Zaitun Zaitun; Ubay Ubay; Nursyam Nursyam; Putri Maharani (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2026)
This study aimed to analyze the application of the communicative language teaching (CLT) method in enhacing Arabic reading skills (maharah al-qira'ah) in students at MTsN 3 Palu. The method used was qualitative using Miles and Huberman's analysis from data of observations, interviewes, and documenties. The results of the study showed that the application of the Communicative Language Teaching (CLT) method in teaching reading skills at MTsN 3 Kota Palu has been proven to have a significant impact on improving students’ communicative and holistic reading abilities through systematic implementation and the use of interactive and meaningful learning strategies. The research findings indicated that the success of CLT is largely determined by systematic teaching implementation through introductory, core, and concluding stages, as well as the use of communicative strategies such as loud reading, repetitive reading, reducing reading anxiety, text chunking, and collaborative reading. This study reinforces CLT’s position as a flexible and contextual approach in Arabic language learning, while also providing a practical contribution in the form of an implementation model that teachers can use as a reference. The strengths of this study lie in its comprehensive and contextual analysis and the integration of religious values into learning.